(3y+5)=(4y-10)

Simple and best practice solution for (3y+5)=(4y-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3y+5)=(4y-10) equation:


Simplifying
(3y + 5) = (4y + -10)

Reorder the terms:
(5 + 3y) = (4y + -10)

Remove parenthesis around (5 + 3y)
5 + 3y = (4y + -10)

Reorder the terms:
5 + 3y = (-10 + 4y)

Remove parenthesis around (-10 + 4y)
5 + 3y = -10 + 4y

Solving
5 + 3y = -10 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
5 + 3y + -4y = -10 + 4y + -4y

Combine like terms: 3y + -4y = -1y
5 + -1y = -10 + 4y + -4y

Combine like terms: 4y + -4y = 0
5 + -1y = -10 + 0
5 + -1y = -10

Add '-5' to each side of the equation.
5 + -5 + -1y = -10 + -5

Combine like terms: 5 + -5 = 0
0 + -1y = -10 + -5
-1y = -10 + -5

Combine like terms: -10 + -5 = -15
-1y = -15

Divide each side by '-1'.
y = 15

Simplifying
y = 15

See similar equations:

| 5x^2=2+3x | | 5w+6-w=2 | | 4x+6=2x^2 | | 5x^2+2=3x | | 0=9x^2-39x+24 | | 25+1.75x=10+3.25x | | 6=y^2+5y | | 125=.005s^2+1.1s | | 2p^2-13p-20= | | -x+6(6x+2)=-2+7(-4+11) | | 0.04(4-1)=0.03(-1+8)+0.04 | | h=40t-5t^2 | | 18x^2+23x-6=0 | | 17n=-4 | | -4(n+3)-6=-2(n-7) | | 4y^2+y-3=0 | | 7r^2+48r-7= | | -(x+11)=9 | | -3(-9+x)=24 | | 3(a+2)=2(a-7) | | 11(4x+11)=-2 | | -4(-3+x)=48 | | 4(x-5)=3x-8 | | 2(-4+a)=-24 | | 6x-7x=12 | | 8g+18=62 | | 2(3+k)=2 | | 8y+328=4y | | 3x+9=42 | | 3(-2-4)=2(5-2+1) | | 3c^2+25c+50=0 | | 11x-6=3x^2 |

Equations solver categories